Maximum Hourly and Daily Concentration Patterns of Urban Jakarta Tropospheric Ozone - Hernani Yulinawati; I Made Indradjaja M Brunner (Jurnal Serambi Engineering, 2024)
Tropospheric ozone is formed through UV radiation from sunlight with NOx and VOC precursors. Continuous O3 measurement data were obtained from US Embassy in Central Jakarta from November 4 2022 to September 30, 2023. The data were analyzed and compared with Indonesian NAAQS for 1-hour and 8-hour. Based on NAAQS, 1-hour O3 concentration is measured between 11:00-14:00; The 8-hour concentration is the average of the 8 hours measurements between 06:00-18:00. Based on the analysis, maximum concentration tends to occur between 11:00-16:00. The 1-hour concentration increased in July-September 2023, while maximum of 103 μg /m3 was recorded on November 4, 2022 at 14:00-15:00. Based on the recorded data, the 8-hour concentration can be calculated as the average of 8 hours concentration between 06:00 to 21:00. The measurement between 10:00-18:00 shows higher average 8-hour ozone concentration compared to other ranges. Lowest value was obtained in between 06:00-14:00. With additional O3 concentration data is expected Jakarta air quality can be more understood. With fast application of Low-Cost Sensor (LCS) for PM2.5, LCS for O3 can be considered to support limited number of AQMS in Jakarta. More O3 measurements needed since this parameter is strongly influenced by local meteorological conditions, contributing NOx and VOC pollutants activities, as well wind movement pattern.